2022
DOI: 10.1002/ajmg.a.62627
|View full text |Cite
|
Sign up to set email alerts
|

Probing the functional consequence and clinical relevance of CD320 p.E88del, a variant in the transcobalamin receptor gene

Abstract: The biological and clinical significance of the p.E88del variant in the transcobalamin receptor, CD320, is unknown. This allele is annotated in ClinVar as likely benign, pathogenic, and of uncertain significance. To determine functional consequence and clinical relevance of this allele, we employed cell culture and genetic association studies.Fibroblasts from 16 CD320 p.E88del homozygotes exhibited reduced binding and uptake of cobalamin. Complete ascertainment of newborns with transiently elevated C3 (propion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…These include competing effects of cobalamin analogue formation in the body, 9 and possibly mutations or epigenetic alterations influencing the transcobalamin receptor. 80,81 An intriguing recent study has demonstrated that (auto)antibodies against the CD320 (transcobalamin) receptor may interfere with the proper uptake of cobalamin into the brain. 82 Long-term studies clearly indicate that treatment with pharmacological doses of B12 and the corresponding increase in serum B12 concentrations do not increase mortality risk.…”
Section: Monitoring Outcome and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…These include competing effects of cobalamin analogue formation in the body, 9 and possibly mutations or epigenetic alterations influencing the transcobalamin receptor. 80,81 An intriguing recent study has demonstrated that (auto)antibodies against the CD320 (transcobalamin) receptor may interfere with the proper uptake of cobalamin into the brain. 82 Long-term studies clearly indicate that treatment with pharmacological doses of B12 and the corresponding increase in serum B12 concentrations do not increase mortality risk.…”
Section: Monitoring Outcome and Follow-upmentioning
confidence: 99%
“…These include competing effects of cobalamin analogue formation in the body, 9 and possibly mutations or epigenetic alterations influencing the transcobalamin receptor. 80,81 An intriguing recent study has demonstrated that (auto)antibodies against the CD320 (transcobalamin) receptor may interfere with the proper uptake of cobalamin into the brain. 82…”
Section: Treatmentmentioning
confidence: 99%
“…The three proteins act in succession, at specific points of the food-to-tissue delivery route. Inherited mutations of genes encoding IF (CBLIF 12,13 ), the IF receptor (CUBN, AMN 13,14 ) and TC (TCN2 15 ) are causative of disease, while the clinical relevance is uncertain for mutations of genes encoding the TC receptor (CD320 16 ) as well as HC (TCN1 17 ), which has no dedicated receptor.…”
Section: Structural Basis Of Cobalamin Absorptionmentioning
confidence: 99%
“…The DSSDE motif is also present in other LDLR-containing cell surface receptors on the apical membrane in renal proximal tubules. CD320, for example, is a transcobalamin receptor for vitamin B12 uptake [55,56]. The N-terminal extracellular region of CD320 contains two LDLR domains, the second of which has a DSSDE motif (Figure 2).…”
Section: Regulation Of Sodium Homeostasis In Non-cardiac Tissuesmentioning
confidence: 99%